2009
DOI: 10.3399/bjgp09x472601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic prescribing strategies and an information leaflet on longer-term reconsultation for acute lower respiratory tract infection

Abstract: Limited evidence suggests that delayed prescribing may influence future consultation behaviour. AimTo assess the effects of antibiotic prescribing strategy on reconsultation in the year following presentation with acute lower respiratory tract infection (LRTI). Design of studyBalanced factorial randomised trial. SettingPrimary care. MethodEight hundred and seven subjects, aged ≥3 years, had acute illness presenting with cough as the main symptom, plus at least one symptom or sign from sputum, chest pain, dyspn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Norway), delayed prescription is perceived by GPs as a practical solution that could help to meet patient needs and avoid seeking after-hours care if their condition worsens [53]. Moreover, a randomised trial [54] demonstrated that delayed prescription is effective in modifying behaviour during follow-up consultations, leading to a lower rate of follow-up consultations among those that had delayed prescriptions as compared to those prescribed right away. Ultimately, formalizing and promoting a delayed approach could become an integral part of an effective rational antibiotic use policy.…”
Section: Discussionmentioning
confidence: 99%
“…Norway), delayed prescription is perceived by GPs as a practical solution that could help to meet patient needs and avoid seeking after-hours care if their condition worsens [53]. Moreover, a randomised trial [54] demonstrated that delayed prescription is effective in modifying behaviour during follow-up consultations, leading to a lower rate of follow-up consultations among those that had delayed prescriptions as compared to those prescribed right away. Ultimately, formalizing and promoting a delayed approach could become an integral part of an effective rational antibiotic use policy.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed prescription strategy, commonly used in the UK but not in the Netherlands, might be particularly suited to preventing these reconsultations without unnecessarily increasing antibiotic prescribing in this group of patients with intermediately elevated CRP values. 10 All together, this stresses the importance of explanation provided to the patient on the implications of CRP values.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…A recent study shows that patients who had been prescribed antibiotics for cough in the previous 2 years were much more likely to reconsult for LRTI. 10 Fewer reconsultations for LRTI decreases workload and will decrease antibiotic prescribing for patients who are at particular risk of unnecessary antibiotic prescribing during reconsultations. Nearly half of all patients were prescribed antibiotics during patient-initiated reconsultations, despite evidence suggesting that they are unlikely to benefit at the point of reconsultation, except for a minority of patients with evident deteriorating illness.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…1 Non-indicated use of antibiotics is furthermore related to unnecessary exposure to adverse effects, costs and patients' re-consultation. 2,3 There is growing concern that therapeutic options become limited if resistance rates continue to rise. The most effective strategy for combating antimicrobial resistance is decreasing antibiotic use.…”
Section: Introductionmentioning
confidence: 99%